LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI KALANGAN PEJABAT PEMERINTAH DAERAH PROVINSI BENGKULU TAHUN 2007 - Emyana Ruth Eritha Sirait (Widyariset, 2009)
Information and Communication Technology (ICT) which has become main component development supporting in various sector nowadays, is used by government to increase government performance through Electronic Government program. One initial step that is needed in developing e-government is e-literacy in ICT field especially in circle of government official as organizer and user of e-government. So, this research is intended to measure government official's ICT literacy, in case ofBengkulu Province regional official, in supporting e-government implementation in the future. The result of this research is supposed to be a reference to arrange some policy in order to increase human resource quality related to e-government. ICT literacy is related and influenced by information literacy, computer literacy, and internet literacy. The result of the research by using survey method shows that in circle of Bengkulu Province government official, information literacy is quite good, computer literacy is still low, and internet literacy is very bad, so by referring to Personal-Capabilty Maturity Model (P-CMM) model, ICT literacy in Bengkulu Province government official is placed in first level.